Restorative Justice in Homicide Cases: Opportunities and Challenges - Jumra; Sandra, Gustika; Rasyid, Mukhawas; Agustafa (Journal of Indonesian Scholars for Social Research, 2024)
Restorative justice is an alternative approach to the criminal justice system that focuses on restoring relationships between offenders, victims and society rather than simply punishment. This research aims to explore the application of restorative justice in murder cases, assessing the extent to which the concept can be applied and its effectiveness in the Indonesian criminal law context. In this discussion, possible opportunities for the application of restorative justice are examined, such as the potential for victim recovery and offender reintegration into society. However, major challenges are also identified, including normative barriers in the law, resistance from law enforcement officials, and social and cultural constraints. This study uses a qualitative approach with juridical analysis of murder cases in Indonesia that consider aspects of restorative justice. The results showed that although restorative justice offers much potential to improve the justice system, its application in homicide cases requires significant legal reform, education and training of law enforcement officers, and a paradigm shift in society. In conclusion, while restorative justice has opportunities to be applied in homicide cases, the challenges present require a holistic approach to ensure effective implementation.